Literacy-related features in repetitions. (21st July 2020) - Arendt, Birte; Zadunaisky Ehrlich, Sara
Abstract : Studies about peer talk have pointed to the centrality of argumentative events in peer interactions and their contribution to children's discourse skills. In this study we focus on and examine repetitive instances in argumentative peer talk with the aim of showing different functions repetitions can fulfil. Since there is relatively little intercultural research in this field, we have conducted an intercultural comparison. For this purpose, we identified events of argumentative character in naturally occurring peer talk of German- and Hebrew-speaking children in Germany and Israel, at kindergarten and pre-school respectively, and conducted a qualitative analysis. The findings indicate that the repetitions in both databases have much in common, displaying similar literacy-related features. In this way, repetitions are an available resource which is significant in events of argumentative nature for language and peer socialization, beyond cultural differences.